Influence of leg preference on bilateral muscle activation during cycling - Carpes, F. P.; Diefenthaeler, F.; Bini, R. R.; Stefanyshyn, D. J.; Faria, I. E.; Mota, C. B. (Journal of Sports Sciences, 2011)
The purpose of this study was to investigate asymmetry of muscle activation in participants with different levels of experience and performance with cycling. Two separate experiments were conducted, one with nine cyclists and one with nine non-cyclists. The experiments involved incremental maximal and sub-maximal constant load cycling tests. Bilateral surface electromyography (EMG) and gross and net muscle efficiency were assessed. Analyses of variance in mixed linear models and t-tests were conducted. The cyclists in Experiment 1 presented higher gross efficiency (P < 0.05), whereas net efficiency did not differ between the two experiments (21.3 ± 1.4% and 19.8 ± 1.0% for cyclists and non-cyclists, respectively). The electrical muscle activity increased significantly with exercise intensity regardless of leg preference in both experiments. The coefficient of variation of EMG indicated main effects of leg in both experiments. The non-preferred leg of non-cyclists (Experiment 2) presented statistically higher variability of muscle activity in the gastrocnemius medialis and vastus lateralis. Our findings suggest similar electrical muscle activity between legs in both cyclists and non-cyclists regardless of exercise intensity. However, EMG variability was asymmetric and appears to be strongly influenced by exercise intensity for cyclists and non-cyclists, especially during sub-maximal intensity. Neural factors per se do not seem to fully explain previous reports of pedalling asymmetries.